Comparing cortical auditory processing in children with typical and atypical benign epilepsy with centrotemporal spikes: Electrophysiologic evidence of the role of non–rapid eye movement sleep abnormalities. (25th March 2015) - Filippini, Melissa; Boni, Antonella; Giannotta, Melania; Pini, Antonella; Russo, Angelo; Musti, Muriel Assunta; Guerra, Angelo; Lassonde, Maryse; Gobbi, Giuseppe
Summary Objective The mismatch negativity (MMN) is an objective measure of central auditory discrimination. MMN alterations have been shown in children with language and/or developmental disorders. In benign focal epilepsies, neuropsychological disorders are often reported and linked to interictal epileptic discharges (IEDs) during non–rapid eye movement (NREM) sleep. There are few studies reporting MMN in children with benign epilepsy with centrotemporal spikes (BECTS) and sleep IEDs. Moreover, no MMN recording has yet been reported in atypical BECTS children with continuous spike‐and‐wave during sleep (CSWS). We retrospectively compared MMN in typical and atypical BECTS children, particularly addressing the impact of NREM sleep IEDs on auditory discrimination. Moreover, we attempted a neuropsychological characterization of patients. Methods The MMN was recorded in 9 normal controls and 23 patients (14 typical BECTS and 9 atypical BECTS) in an oddball paradigm with syllable stimuli. MMN, sleep electroencephalography (EEG) and neuropsychological evaluation were realized in the same testing session. Results Measurable MMN responses to speech stimuli were identified in both the control and patient groups. A significant difference between control and atypical BECTS children was found with respect to amplitude (p = 0.0061). Atypical BECTS also showed a lower MMN amplitude with respect to typical BECTS, but this difference did not reach statistical significance (p = 0.0545). Statistical comparisons between groups revealed no differences in latency. Among the neuropsychological variables, academic difficulties were significantly more prominent in the patients with atypical BECTS (p = 0.04). Significance CSWS EEG pattern affects auditory discrimination and may have a long‐lasting impact on academic skills acquisition, whereas in typical BECTS children with a lower degree of IED NREM sleep, plastic brain reorganization or the preservation of participating networks may prevent such difficulty. Early electrophysiologic identification of auditory discrimination deficits in epileptic children could be used in early rehabilitation, thereby reducing the risk of developing neuropsychological disorders.